Effects of dissolved organic matter on mercury speciation in rice rhizosphere amended with sulfur-rich biochar - Hualing Hu; Yiman Gao; Wenbing Tan; Beidou Xi (Soil & Environmental Health, 2023)
Natural sulfur (S)-rich biochar (NRB) can be employed as an alternative for traditional S-modified biochar. However, the effect of dissolved organic matter (DOM) on mercury (Hg) speciation in rice rhizosphere soils under natural S-rich biochar application remains unclear. We conducted a pot experiment to study the effects of NRB application on the chemical composition and structure of DOM and the related speciation and availability of Hg in rice rhizosphere. Applying NRB significantly increased the concentration of methylmercury (MeHg) in the rhizosphere soils, which was enhanced with application frequency. This observation can be explained by MeHg immobilization in response to increasing S content in rice rhizosphere soils. We also observed increased molecular weight and functional group complexity of DOM, likely contributing to the decrease in MeHg mobility. Furthermore, the increase in pH and humification of DOM caused by S-rich biochar application generally reduced the concentrations of water-soluble and mercuric-sulfide fraction (easily-available Hg species) and organo-chelated fraction (potentially-available Hg species). Our findings highlight that the application of NRB can reduce the availability of MeHg in rice rhizosphere, thus providing a practical basis for reducing the potential risk of MeHg toxicity.